Biometric key generation using crow algorithm - Zied O. Ahmed; Abbas Akram Khorsheed (Institute of Advanced Engineering and Science, 2021)
The researchers have been exploring methods to use biometric characteristics of the user as a replacement for using unforgettable pass-word, in an attempt to build robust cryptographic keys, because, human users detect difficulties to call up long cryptographic keys. Biometric recognition provides an authentic solution to the authentication of the user problem in the identity administration systems. With the extensive utilization of biometric methods in different applications, there is growing concern about the confidentiality and security of the biometric technologies. This paper proposes biometric based key recreation scheme. Since human ears are not correlated. Until now, the encryption keys are generated using a swarm intelligence approach. Collective intelligence of simple groups of autonomous agents have been emerged by swarm intelligence. The crow search algorithm which is known as (CSA) is a new meta-intuitive method assembled by the intelligent group behavior of crows. Despite that CSA demonstrates important features, its search approach poses excessive challenges while faced with great multimodal formularization.